Annotating new genes : from in silico screening to experimental validation - Uchida, Shizuka (Woodhead Publishing series in biomedicine, 2012)
Annotating new genes outlines an approach to the analysis of evolutionary-conserved, heart-enriched genes with unknown functions, offering a step-by-step description of the procedure from screening to validation. The book begins by offering an introduction to the databases and software available, before moving on to cover programming guidelines, including a specific case study on the use of C-It for in silico screening. The second half of the book offers a step-by-step guide to experimental validation concepts and procedures, as well as an overview of additional potential applications of this approach in the field of stem cells and tissue regeneration, before a concluding chapter summarises the concepts and theories presented.